Serum level of Total Antioxidant Status and Malondialdehyde in the Patients with Polycystic Ovarian Syndrome: a Comparative Study - Magar , Bibek Pun; Magar , Dilli Pun; Amgain, Kapil; Joshi, Keshavraj; Satyal , Niranjan; Oli , Jharendra Bahadur (Europasian Journal of Medical Sciences, 2021)
Background: Polycystic ovary syndrome (PCOS) is a complex endocrine disorder in women of reproductive age and a major cause of infertility. Anti- Mullerian Hormone (AMH), a valid marker of ovarian function, is used for the diagnosis of PCOS. The aim of this study is to assess the serum level of total antioxidant status (TAS) and malondialdehyde (MDA) in the premenopausal women with PCOS. Methods: A cross-sectional analytical study was conducted at Padmashree Diagnostics, Department of Gynecology, India from April 2016 to March 2017. Census method was used to select the samples. The oxidative stress was measured by measuring the level of TAS and MDA. The data was recorded in structured proforma and and enter in SPSS version 16.0. The data were expressed in frequency, percentage, mean and standard deviation and the results obtained were analyzed using pearson’s correlation and student’s t-test. The p-value less than 0.05 was taken as statistically significant. Results: The measured serum AMH level among the patients with PCOS was within normal range in 67.5% (27) and above normal range in 32.5% (13). The serum TAS level in normal AMH group was 814.0 + 291 µMol/L and in above normal range group was 720 + 240 µMol/L, (p <0.001). Similarly, the serum level of MDA in normal AMH group was 6.64 + 0.21 µMol/L, and in above normal range group was 8.78 + 0.22 µMol/L (p = 0.01). The measured level of AMH was significantly associated with the increased level of MDA (p<0.001) and decreased level of TAS (p<0.001). The measured MDA level in high AMH group did show statistically significant than the normal AMH group. Conclusions: Serum level of TAS and MDA along with AMH are valuable diagnostic biomarker for the diagnosis of PCOS in the resource poor settings where ultrasound facility is unavailable. DOI: https://doi.org/10.46405/ejms.v3i2.367